Hubungan antara Kepribadian dan Resolusi Konflik Interpersonal dengan Teman Sebaya pada Remaja di Makassar - Andi Tenri Faradiba (Fakultas Psikologi Universitas Pancasila, 2016)
The aim of this study was examined correlation between personality and interpersonal conflict resolution with friends using one tail hypothesized. This study was quantitative research using personality and interpersonal conflict resolution as variables. The personality is explained by Five-Factor Model and measured using NEO-Five Factor Inventory: openness to experience, conscientiousness, extraversion, agreeableness, and neuroticism. Interpersonal conflict resolution is explained as an effort to resolve conflict and measured using vignette. The participants were 154 adolescents in Makassar. There was a significant negative correlation between conscientiousness and power assertion. On the other hand, there was a significant positive correlation between neuroticism and power assertion. Adolescents in Makassar with low conscientiousness tend to use disengagement for resolving the interpersonal conflict with their friends.